Vaccines as a Strategy to Control Trichinellosis - Tang, Bin; Li, Jian; Li, Tingting; Xie, Yiting; Guan, Wei; Zhao, Yanqing; Yang, Shuguo; Liu, Mingyuan; Xu, Daoxiu (Frontiers in Microbiology, 2022)
Trichinellosis caused by Trichinella spiralis nematodes is a worldwide food-borne parasitic zoonosis. Several approaches have been performed to control T. spiralis infection, including veterinary vaccines for animals, which contribute to improving animal health and increasing public health by preventing trichinellosis transmission from animals to humans. In the past several decades, many vaccine studies have been performed in effort to control T. spiralis infection by reducing the muscle larvae and adult worm burden. Various candidate antigens, selected from excretory-secretory (ES) products and different functional proteins involved in the process of establishing infection have been investigated in rodent or pig models to explore their protective effect against T. spiralis infection. Moreover, different types of vaccines have been developed to improve the protective effect against T. spiralis infection in rodent or pig models, such as live attenuated vaccines, natural antigen vaccines, recombinant protein vaccines, DNA vaccines and synthesized epitope vaccines. However, few studies of T. spiralis vaccines have been performed in pig, and future research should focus on exploring the protective effect of different types of vaccines in these models. Here, we present an overview of the strategies for the development of effective T. spiralis vaccines and summarize the factors of influencing the effectiveness of vaccines. We also discuss several propositions in improving the effectiveness of vaccines and may provide a route map for future T. spiralis vaccines development.